Identification of the midline by obese and non‐obese women during late pregnancy1. (3rd September 2014) - Butcher, M.; George, R. T.; Ip, J.; Campbell, J. P.; Yentis, S. M.
Summary During central neuraxial blockade, identifying the midline in parturients can be difficult, particularly if they are obese. We assessed the ability of women in late pregnancy, both obese and non‐obese, to identify the midline of their own back by pointing and by pinprick discrimination with reference to the true midline identified by ultrasound. Thirteen out of 25 (52%) obese women were accurate to within 5 mm in identifying the midline of their back by pointing with their fingertip, compared with 21/25 (84%) non‐obese women (p = 0.03). The median (IQR [range]) fingertip‐midline distance was greater in obese women (5 (5–10 [0–10]) mm compared with non‐obese women (2 (0–5 [0–12]) mm; p = 0.007). Identification of the midline using pinprick was poorer by obese women (median (IQR [range]) 33 (25–45 [3–85]) mm) than by non‐obese women (18 (13–25 [8–40]) mm; p < 0.0001). However, women in both groups were correct > 99% of the time in identifying that a stimulus was either to the left or to the right side.